Credit Enhancement and Performance of Hydroelectric Energy Projects in Kenya - Amolo, Amolo Elvis Juma; Rambo, Charles Mallans; Wafula, Charles Misiko (International journal of finance & banking studies, 2020)
Renewable energy investment has been underexploited in Africa and Kenya in specific due to financing constraints arising from investor’s negative perception of the regions high investment risk and low creditworthiness which retards the degree of private capital penetration. The purpose of the study was to assess the extent to which Credit enhancement influence performance of hydroelectric energy projects in Kenya. The study was underpinned on pragmatism paradigm which allows the use of mixed method approach and descriptive correlational survey research design. Structured questionnaires and interview guide were used to collect quantitative and qualitative data from a sample size of 94 participants out of a target population of 94 subjects. Validity test was done on the instruments and a coefficient of 0.775 obtained using Content Validity Index while reliability involved pretesting of the instruments amongst the 10% of the participants and Cronbach's alpha coefficient of 0.781 obtained. Analysis was done using both descriptive statistic of mean and standard deviation and inferential statistic of Correlation and Regression at a significance level of 0.05 with the aid of SPSS version 25 and thematic content analysis of qualitative data for triangulation. Simple linear regression and Pearson Correlation Coefficient models were used to determine the influence between independent and dependent variable and the result H0: Credit enhancement does not significantly influence performance of hydroelectric energy projects in Kenya was rejected since P=0.000<0.05.Therefore the study concluded that there is significant influence of credit enhancement on performance of hydroelectric energy projects in Kenya. It is recommended that Project management and policy makers should integrate appropriate credit enhancement instruments to improve performance of hydroelectric energy projects besides developing targeted policies for strengthening implementation of the credit enhancement instruments to boost investors and lenders confidence. Further research should be carried out on the determinants influencing effective utilization of credit enhancement in power projects in Kenya.